Protective efficacy of vitamin b12 combined with far-infrared radiation on radiation-induced skin damage in the treatment of pelvic tumours. (2015) - Ge, Qin; , Cen-ming Yu; , Jing Cai; , Chun-xia Chu; , Guo-dong Xie; Zhao, Ji-Zhong
No abstract available